RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN MENTIMUN (Cucumis sativus L.) AKIBAT PEMBERIAN PUPUK KANDANG SAPI DAN PUPUK ORGANIK PADAT SUPERNASA - Yusri Fefiani; Wan Arfiani Barus (AGRIUM: Jurnal Ilmu Pertanian, 2014)
This research was conducted to investigate the production and growth response of cucumber with adopted of cow manure and supernasa solid fertilizer in the field trials of Agricultural Faculty of North Sumatera Muhammadiyah University, altitude of 27 m above sea level with a factorial randomized, block design with two treatment factors were manure factor (K) in 3 rate treatments is 0; 3,6; 7,2 kg/plotting notated as K0, K1, K2. While the second factors were supernasa solid fertlizer (S) in 4 rate treatments is  0; 2,7; 5,4; 8,1 gr/plotting notated as S0, S1, S2, S3. Variables measured were plant height, fruit height, fruit diameter, planting fruit weight and number of fruit crops. The result of the reseach was 7,2 kg/plotting cow manure has significant effect on the variables plant height ang fruit height but weren’t significant for another variables. Provision of 8,1 gr/plotting supernasa solid fertilizer has significant effect on the variables fruit height, fruit diameter and planting fruit weight, but weren’t significant for another variables. Interaction of cow manure and supernasa solid fertilizer hasn’t significant for all treatments. Keywords : supernasa fertilizer, cow manure, production, growth, cucumber